DETERMINATION AND STRATEGY OF SUPERIOR FOOD DEVELOPMENT BASED ON PRODUCTION IN BANGGAI ISLANDS REGENCY - Katili, Hidayat Arismunandar; Sariani, Sariani; Puspapratiwi, Dian; Enteding, Trianto (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2024)
Sustainable agriculture has a role in improving the living standards of farmers and the welfare of their communities. The purpose of this study is to identify superior food commodities and determine the strategy for their development in the Banggai Islands Regency. This study used Location Quotient (LQ), Ship Share Analysis (SSA), and SWOT approaches. The research results from determining competitive and comparative superior food commodities in the Banggai Islands Regency, namely cassava, taro, and sweet potatoes, were obtained from Banggai plants in 5 sub-districts, then sweet potato plants were obtained in 3 districts, and corn and peanut plants. the harvest was obtained by 1 district. Furthermore, the strategy for developing superior food crop commodities in Banggai Islands Regency is Strategy (ST), namely utilizing farmers' experience in farming, the ability to manage land to overcome the limitations of agricultural machinery, increasing the role of combined farmer groups which have not been maximized to reduce high labor wages. Next, utilize the availability of food crop commodity seed stocks to overcome the procurement of superior food crop seeds which are difficult to obtain. In addition, local governments are advised to encourage efforts to intensify superior agriculture by implementing strategies and directives following this research and are expected to improve facilities for farmers' needs to obtain better production and crop productivity in the future. With the results obtained, there is a need for the government's role as a facilitator for farmers in overcoming obstacles and fulfilling solutions based on the strategies obtained.